Outstanding Outcome of Pancreatic Cancer: What Lessons Do We Learn - Muhammad W. Saif, MD (Pancreas, 2025)
The American Cancer Society’s estimates that 57,600 people (30,400 men and 27,200 women) will be diagnosed with pan-creatic cancer in the United States for 2020 and approximately 47,050 people (24,640 men and 22,410 women) will die of pancre-atic cancer in 2020.1 Despite advances in first-line therapy such as gemcitabine/nab-paclitaxel and fluorouracil, leucovorin, oxalipla-tin, and irinotecan (FOLFIRINOX) in advanced pancreatic cancer (aPC), median overall survival remains less than 12-months.